Clinical immunology and serology: a laboratory perspective - Stevens, Christine Dorresteyn; Miller, Linda E. (Philadelphia, Pennsylvania : F. A. Davis Company, 2017)
The perfect balance of theory and practice! Here$1 (Bs the must-have information you need to understand the essential principles of immunology and to master the serology techniques most commonly used in the laboratory. Easy-to-read, student-friendly coverage focuses on the direct application of theory to clinical laboratory practice, preparing you for the real world in which you will practice. The 4th Edition of this popular text has been completely updated and revised throughout to reflect the latest advances in the field. A brand-new full-color layout makes the content easier to understand than ever before.s
Introduction to immunity and the immune system -- Nature of antigens and the major histocompatibility complex -- Innate immunity -- Adaptive immunity -- Antibody structure and function -- Cytokines -- Complement system -- Safety and quality assurance -- Principles of serologic testing -- Precipitation and agglutination reactions -- Labeled immunoassays -- Molecular diagnostic techniques -- Flow cytometry and laboratory automation -- Hypersensitivity -- Autoimmunity -- Transplantation immunology (old 18) -- Tumor immunology (old 19) -- Immunoproliferative diseases (old 16) -- Immunodeficiency diseases (old 17) -- Serological and molecular detection of bacterial infections -- Spirochete diseases -- Serological and molecular diagnosis of parasitic and fungal infections -- Serology and molecular detection of viral infections -- Laboratory diagnosis of hiv infection -- Immunization and vaccines.
Includes bibliographical references and index.
Keywords: CLINICAL IMMUNOLOGY